Peran Dompet Dhuafa Wasapada Dalam Memberikan Program Pendidikan Kepada Anak-Anak Kurang Mampu Di Kota Medan - Zuhrinal M. Nawawi; Feby Maulydia Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
There are still many children from underprivileged families or poor people who are forced to drop out of school due to lack of funds. This study aims to determine the role of Dompet Dhuafa Waspada in providing solutions or educational programs to address educational inequality for underprivileged children in Medan City. This research is classified as a qualitative research and uses a literature study data collection method. The results of the study show that Dompet Dhuafa Waspada Medan City has several programs to improve the quality of education for underprivileged children, namely Bintang Rabbani School, Success Scholarship and SMART Ekselensia. Keywords: Dompet Dhuafa, Medan, Zakat